Linguistic challenges of pre-service teachers in English medium instruction and its relationship to their teaching self-efficacy beliefs - Dzormeku, Charles Selorm (Elsevier Ltd, 2025)
Using a latent profile analysis, we attempted to categorize Ghanaian pre-service teachers according to the levels of their English language linguistic challenges and to investigate how these challenges relate to their teaching self-efficacy beliefs. A sequential mixed method approach was adopted, surveying 300 participants and followed by eight interviews. We found that speaking skills were the most challenging for the participants. Qualitative results revealed that the participants have limited vocabulary, difficulty in developing coherent paragraphs, challenges with pronunciation, inadequate orthographic knowledge, and grammatical challenges. We observed that the higher the participants’ linguistic challenges, the lower their self-efficacy beliefs.